Assessment of pain‐related behavior and pro‐inflammatory cytokine levels in the rat rotator cuff tear model. Issue 2 (9th September 2013) - Yamazaki, Hironori; Ochiai, Nobuyasu; Kenmoku, Tomonori; Ohtori, Seiji; Sasho, Takahisa; Miyagi, Masayuki; Ishikawa, Tetsuhiro; Kamoda, Hiroto; Orita, Sumihisa; Sasaki, Yuu; Yamaguchi, Takeshi; Kijima, Takehiro; et al.
Abstract The cause of pain following rotator cuff tear has not been fully elucidated. The purpose of this study was to evaluate behavior and inflammatory cytokines in a rat unstabilized rotator cuff defect (UCD) model. Forty‐five Sprague–Dawley rats were divided into three groups: sham; UCD; and stabilized rotator cuff defect (SCD). Gait analysis was examined using CatWalk. Tumor necrosis factor (TNF)‐α, interleukin(IL)‐1β, and IL‐6 were measured within the subacromial bursa and the glenohumeral joint synovium at 21 and 56 days after surgery using an enzyme‐linked immunosorbent assay (ELISA). Stride length, print area and contact intensity in the UCD group was significantly lower than in the sham group after surgery. Stride length, print area and contact intensity in the SCD group was significantly higher than in the UCD group. In contrast, TNF‐α, IL‐1β, and IL‐6 in the UCD group was significantly higher than in the sham group at days 21 and 56. However, TNF‐α, IL‐1β, and IL‐6 in the SCD group was significantly lower than in the UCD group at days 21 and 56. The present results suggest that SCD is effective not only in improving shoulder function but also in reducing inflammatory cytokines, which may serve as one source of pain due to rotator cuff tear. © 2013 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 32:286–290, 2014.